2011
DOI: 10.1097/smj.0b013e3182242eaa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodontal Treatment on Lipoproteins Levels in Plasma in Patients with Periodontitis

Abstract: This pilot study shows that periodontal disease significantly affects the serum levels of lipoproteins and suggests that following successful periodontal treatment decreases serum lipid concentration. This study suggests also that lipoproteins are possible intermediate factors that may link periodontal disease to elevated cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
3
25
0
3
Order By: Relevance
“…Some authors [16,22,23] found that periodontal disease (PD) is a possible causal factor of heart disease, whereas Joshipura et al [19] reported that the strength of the evidence for this biologically plausible association was found to be insufficient but suggestive of a causal relationship. In another study Pejcic et al [21] was found a significant relation between indicators of poor periodontal status, such as PPD, CAL, gingival bleeding index, and serum level lipoproteins. These findings suggested that lipoproteins are possible intermediate factors that may link PD to elevated cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors [16,22,23] found that periodontal disease (PD) is a possible causal factor of heart disease, whereas Joshipura et al [19] reported that the strength of the evidence for this biologically plausible association was found to be insufficient but suggestive of a causal relationship. In another study Pejcic et al [21] was found a significant relation between indicators of poor periodontal status, such as PPD, CAL, gingival bleeding index, and serum level lipoproteins. These findings suggested that lipoproteins are possible intermediate factors that may link PD to elevated cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Significant associations between periodontitis and CHD have been reported in previous case-control and cohort studies [8,10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], which are dependent on the severity of periodontal disease (PD) [10,31]. This could be directly due to periodontal pathogens or their products on endothelial cells via transient bacteremia or indirectly due to products on the inflammatory response, central role in pathogenesis of CVD [32].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…sa površinom zahvaćenog tkiva u parodontopatiji. U cirkulaciji, LPS sarađuju sa svim klasama lipoproteina i mogu inicirati aterogenezu, kada se transportuju u arterijski zid sa LDL-om 24 . Američka akademija parodontologa poziva ljude koji imaju rizik za pojavu kardiovaskularnih bolesti ili imaju znake oboljenja gingive da se konsultuju sa stomatolozima-parodontolozima radi lečenja parodontalnih oboljenja 25 .…”
Section: The Link Between Gum Disease and Heart Disease (Attack And Sunclassified
“…Therefore, for the first time to our knowledge, it has been shown that high serum concentrations of LPS are actually associated with the area of affected tissue in periodontitis. In circulation, LPS associates with all lipoprotein classes and it may initiate atherogenesis, when it is transported into the arterial wall with LDL 24 . The American Academy of Periodontology appeals to people who are at risk for cardiovascular disease or have signs of gum disease to consult a dentist having ehperience in treating periodontal disease 25 .…”
Section: Trudnoća I Parodontopatijamentioning
confidence: 99%